Assessing changes in the atmospheric water budget as drivers for precipitation change over two CORDEX-CORE domains - Llopart, Marta [UNESP]; Domingues, Leonardo Moreno; Torma, Csaba; Giorgi, Filippo; da Rocha, Rosmeri Porfírio; Ambrizzi, Tércio; Reboita, Michelle Simões; Alves, Lincoln Muniz; Coppola, Erika; da Silva, Maria Leidinice; de Souza, Diego Oliveira (Springer Nature, 2020)
This study evaluates the projected changes in the atmospheric water budget and precipitation under the RCP8.5 scenario over two CORDEX-CORE domains: South America (SAM) and Europe (EUR). An ensemble of five twenty-first century projections with the Regional Climate Model version 4 (RegCM4) and their driving Global Climate Models (GCMs) are analyzed in terms of the atmospheric water budget terms (precipitation, P; evapotranspiration, ET; and moisture flux convergence, C). Special focus is on four subregions: Amazon (AMZ), La Plata basin (LPB), Mid-Europe (ME) and Eastern Europe (EA). The precipitation change signal in SAM presents a dipole pattern, i.e. drier conditions in AMZ and wetter conditions in LPB. Over the two European regions a seasonality is evident, with an increase of ~ 25% in precipitation for DJF and a decrease of ~ 35% in JJA. The atmospheric water budget drivers of precipitation change vary by region and season. For example, in DJF the main drivers are related to the large-scale moisture flux convergence, while in JJA over the AMZ atmospheric moisture flux convergence plays only a minor role and local processes dominate. For JJA in the GCMs the high values of the residual term do not allow us to assess which mechanisms drive the precipitation change signal over the AMZ and LPB, respectively. Same conclusions are found for the RegCM4 JJA simulations over the LPB and EA. This points to the importance of the spatial resolution of climate simulations and the role of parameterization schemes in climate models. Our work illustrates the usefulness of analyzing regional water budgets for a better understanding of precipitation change patterns around our globe.
Keywords: Atmospheric water balance; Climate change; CORDEX-CORE; RegCM4